Hydrophobic ceramic membrane for membrane distillation: A mini review on preparation, characterization, and applications - Hubadillah, Siti Khadijah; Zhong, Sheng Tai; Othman, Mohd Hafiz Dzarfan; Harun, Zawati; Jamalludin, Mohd Riduan; A. Rahman, Mukhlis; Jaafar, Juhana; Ismail, Ahmad Fauzi (Elsevier, 2019)
Membrane distillation (MD) is one of the emerging separation technologies with extremely high separation factor, especially in desalination application. MD utilizes the hydrophobic membrane which only allows the passage of vapor through the membrane pores. Recent years have witnessed great progress in the development of hydrophobic ceramic membranes for MD applications due to their superior properties over the polymeric counterparts. However, ceramic membranes are hydrophilic in nature; hence, membrane surface modification process is required to acquire hydrophobic properties for MD applications. Direct grafting using silane agents is the most widely used ceramic membrane hydrophobization method. Hence, this mini review provides a complete summary of the research progress on the preparation and characterization of the hydrophobic ceramic membranes through silane agent grafting, as well as their applications in MD. Finally, future research directions have also been addressed.